Improving quality in national reference laboratories: The role of SLMTA and mentorship - Rosemary A. Audu; Catherine C. Onubogu; Nkiru N. Nwokoye; Eke Ofuche; Shirematee Baboolal; Odafen Oke; Elizabeth T. Luman; Emmanuel O. Idigbe (AOSIS, 2014)
Background: The Nigerian Institute of Medical Research houses two reference laboratories: the virology and tuberculosis laboratories. Both were enrolled in the Strengthening Laboratory Management Toward Accreditation (SLMTA) programme. Objective: To describe the impact of SLMTA and discuss factors affecting the results, with an emphasis on mentorship. Methods: The SLMTA programme was implemented from April 2010 through November 2012. Participants attended three workshops and executed quality improvement projects; laboratory auditors evaluated performance using a standard checklist. The virology laboratory did not receive mentorship; however, the tuberculosis laboratory had an international mentor who visited the laboratory four times during the programme, spending two to four weeks embedded within the laboratory during each visit. Results: There was an overall improvement in the performance of both laboratories, with the virology laboratory increasing 13% (from 80% at baseline to 93% at exit audit) and the tuberculosis laboratory increasing 29% (from 66% to 95%). These scores were maintained nine months later at the surveillance audit. Conclusion: The SLMTA programme resulted in improved and sustained quality management performance for both laboratories. Mentoring was a possible factor in the substantial improvement made by the tuberculosis laboratory and should be considered in order to augment the training received from the SLMTA workshops.